2020
DOI: 10.1007/s10899-020-09978-7
|View full text |Cite
|
Sign up to set email alerts
|

Reaching Out to Big Losers: How Different Types of Gamblers are Affected by a Brief Motivational Contact Initiated by the Gambling Provider

Abstract: Telephone and letter-based motivational interventions with high expenditure gamblers have significant short and long term positive effects on gambling and use of responsible gambling tools. This report examines how different subtypes of gamblers, based upon patterns of play, are differentially affected. A randomized controlled trial design with three conditions (n = 1003 in each): feedback intervention by letter, telephone or a no-contact control condition. Subtypes of gamblers were derived by latent class ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(26 citation statements)
references
References 21 publications
3
23
0
Order By: Relevance
“…Among them, 1440 were successfully reached, 1542 could not be reached, and 250 individuals were reached but refused to have this motivational intervention (in addition, 30 further individuals were reached but were unable, for other reasons, to have the conversation). Thus, the group reached by the intervention and the control group exceed the size of the two active conditions compared in the Norwegian study by Jonsson et al [20], which demonstrated significant differences between the conditions. Also, for example, a predicted modest increase in self-exclusion from 15% of control individuals to 20% of intervention individuals would require two groups of 905 individuals, respectively, for a significant difference to be demonstrated on a p = 0.05 level.…”
Section: Power Calculationmentioning
confidence: 66%
See 2 more Smart Citations
“…Among them, 1440 were successfully reached, 1542 could not be reached, and 250 individuals were reached but refused to have this motivational intervention (in addition, 30 further individuals were reached but were unable, for other reasons, to have the conversation). Thus, the group reached by the intervention and the control group exceed the size of the two active conditions compared in the Norwegian study by Jonsson et al [20], which demonstrated significant differences between the conditions. Also, for example, a predicted modest increase in self-exclusion from 15% of control individuals to 20% of intervention individuals would require two groups of 905 individuals, respectively, for a significant difference to be demonstrated on a p = 0.05 level.…”
Section: Power Calculationmentioning
confidence: 66%
“…In a randomized study of strategies to contact gamblers with high losses [18], which, in anonymized subjects, followed the gambling operator's own registers, the post-intervention reduction in theoretical gambling loss during 12 months was significantly larger after receiving a telephone intervention compared to a postal letter intervention and compared to a nonintervention control group [19]. Also, a sub-study from the project demonstrated that, within the database of the company assessed, an effect was seen on lottery gamblers even from the postal letter intervention, although, for potentially more addictive gambling types, such as casino gambling and electronic gambling machines, the intervention by telephone was more effective [20]. In this study, however, individuals could not be followed with self-report data, and therefore, data were not able to describe gambling on other gambling operators apart from the one responsible for the intervention.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Altogether, the present study adds to and resembles the conclusions by Ivanova and co-workers [11], who reported that negative reactions to a responsible gambling intervention were possible but rare. Also, the study adds to the promising ndings seen in studies conducted with the Norwegian state-owned gambling operator, and where a telephone intervention was more effective in reducing gambling problems than a control condition or a postal intervention [4,8,9]. Thus, the study adds to the rationale behind introducing active harm-reducing intervention programs in other gambling operators.…”
Section: Discussionmentioning
confidence: 80%
“…Likewise, in a similar project in Norway, the state-owned gambling operator carried out motivational contact attempts addressing subjects with intense gambling practices, in that case de ned as the proportion of the operator's clients with the highest net losses. Here, a personal telephone intervention was more e cacious in reducing high-risk gambling practices, compared to a postal letter contact or a control group [8,9]. Both analyses, however, are limited by the fact that only the own operator's gambling data can be measured, such that gambling on either gambling operators cannot be assessed.…”
Section: Introductionmentioning
confidence: 99%